THE ROLE OF PSYCHOLOGY IN TEACHING FOREIGN LANGUAGES - I. G. Chebotarova (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2014)
The article deals with psychological aspects in the process of foreign language mastering. It studies the role of Psychology in education and its relationship with Pedagogy and Linguistics. The article presents some historical facts of applying psychological theories in foreign language teaching underlining the importance of a teacher's professional language competence, factors of accounting of educational subject particularities and individual peculiarities of learners, especially motivation in learning foreign languages. This article gives psychological and pedagogical analysis of education with the main factors and components. The paper presents the definition of Pedagogical psychology, its close relationship with developmental and age psychology. The author defines the main parts of Pedagogical psychology and shows the significance of Educational psychology in the teaching process and its role in the foreign language mastering. The article gives its interrelation with other disciplines. The author underlines the significance of theories of human development for educational psychology and analyzes the main stages in the organization of work of every teacher. The role of two main aspects in the process of teaching - teaching and educating that are closely interconnected is considered. The paper presents the characteristic of the stages in the process of improving the intelligence of teaching.